CENTRAL MARINE FISHERIES RESEARCH STATION, MANDAPAM CAMP, S. INDIA - Mandapam, Central Mrine Fisheries Research Station (Indian Journal of Fisheries, 2016)
THE Central Marine Fisheries Research Station at Mandapam is one of therecently established Central Institutes of the Government of India underthe Ministry of Food and Agriculture. The Institution was started in 1947with temporary laboratory accommodation provided by the University ofMadras. The headquarters at Mandapam was set up in 1949 when thebuildings constructed originally as a naval hospital by the Defence Departmentduring World War II, were acquired and converted into laboratoriesand temporary residences for the staff. Subsequently an aquarium was builtand circulating sea-water facilities were provided for keeping marine organismsfor study. A capital expenditure of about Rs. 6| lakhs has beenincurred on the Station up to 1952-53. About a hundred acres of landadjoining the Institute has been acquired for expansion of the Station andfor building permanent residences which will form a small self-containedcolony. About ninety acres of land and the road leading to the site are beingacquired at Mandapam on the Palk Bay side, for setting up an experimentalMarine Fish Farm.